2009
DOI: 10.1167/iovs.08-2321
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1: Contribution to Retinal Ganglion Cell Apoptosis and Increased Intracellular Ca2+with Exposure to Hydrostatic Pressure

Abstract: Purpose Elevated hydrostatic pressure induces retinal ganglion cell (RGC) apoptosis in culture. The authors investigated whether the transient receptor potential vanilloid 1 (TRPV1) channel, which contributes to pressure sensing and Ca2+-dependent cell death in other systems, also contributes to pressure-induced RGC death and whether this contribution involves Ca2+. Methods trpv1 mRNA expression in RGCs was probed with the use of PCR and TRPV1 protein localization through immunocytochemistry. Subunit-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
196
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 176 publications
(213 citation statements)
references
References 118 publications
15
196
0
2
Order By: Relevance
“…3). Thus, sensitivity to IOP is an added stressor to other age-related factors (35). A small number of younger DBA/2 (3-5 mo) had transport deficits without IOP elevation (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…3). Thus, sensitivity to IOP is an added stressor to other age-related factors (35). A small number of younger DBA/2 (3-5 mo) had transport deficits without IOP elevation (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…An important hypothesis in glaucoma posits trophic deprivation proximally at the optic nerve head along with loss of axonal integrity (5)(6)(7)(8)43). Myriad somatic and dendritic factors are also likely to contribute, including intrinsic pressure sensitivity and synapse elimination (35,44). Importantly, transport loss at distal sites is predegenerative in that much of the structure of the retinal projection remains intact for a period afterward.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that chemical guidance of growth cones is mediated by an asymmetric influx of calcium ions Ca 2+ ) and the neuronal transient receptor potential (TRP) channels appear to be the key sensors and mediators in the process (Wang and Poo, 2005;Talavera et al, 2008;Li et al, 2005;Sappington et al, 2009). It is know that TRP channels can be activated by depolarization of the cell using chemical guidance factors or by an increase in temperature (Talavera et al, 2008;Caterina et al, 1997) and highly localized heating (Huang et al, 2010), and there is strong evidence in general that depolarization of the neuronal membrane is highly sensitive to small variations in thermodynamic variables like temperature and pressure (Wunderlich et al, 2009;Blicher et al, 2009;Andersen et al, 2009;Wodzinska et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Учитывая известные механизмы патоге-неза глаукомы и ПЭС, витамин D, в условиях его дефицита, может оказывать влияние на скорость и степень обновления внеклеточного матрикса, прогрессию апоптоза ганглиозных клеток сетчат-ки, а также на состояние эндотелия и базальных мембран сосудов и структур, имеющих отноше-ние как к гидродинамике глаза, так и к продукции псевдоэксфолиативного материала, приводя к на-рушениям, выявляемым при ПЭС/ПЭГ [10,18,21,30].…”
Section: Discussionunclassified